RESPONSE OF MUNGBEAN (VIGNA RADIATA) TO PHOSPHATIC FERTILIZER UNDER ARID CLIMATE - M. A. Ali; G. Abbas; Q. Mohy-ud-Din; K. Ullah G. Abbas; M. Aslam (Journal of Animal and Plant Sciences, 2010)
Phosphatic fertilizer has a great importance for Mungbean. It not only increases the yield and yield components of the crop but also improve the quality of the proroduce. A Field experiments were conducted under Adaptive Research Station, to evaluate the influence of three levels of phosphatic fertilizer on mung at Mianwali for two consecutive kharif seasons i.e. 2007 and 2008. The experiment comprised of four treatments viz, control, Phosphatic fertilizer @ 30 Kg ha-1 with started dose of nitrogen, Phosphatic fertilizer @ 57 Kg ha-1and Phosphatic fertilizer @ 84 Kg ha-1. Experiments were laid in randomized complete block design with three replications. The results revealed that all the levels of phosphatic fertilizer showed significant impact on mung compared to that of control plots, However, treatment of Phosphatic fertilizer @ 84 Kg ha-1 out yielded rest of the treatments giving the maximum yield components and grain yield during both years.
Keywords: Mungbean (Vigna radiata); phosphatic fertilizer; arid; gain yield; Pakistan